Kinetics of antifungal activity of home-generated ozonated water on Candida albicans - Amirtaher Mirmortazavi; Hamidreza Rajati Haghi; Abdolmajid Fata; Hossein Zarrinfar; Hossein Bagheri; Amirhossein Mehranfard (Mazandaran University of Medical Sciences, 2018)
Background and Purpose: Candida-associated denture stomatitis is one of the most common forms of oral candidiasis among denture wearers. Regarding this, the aim of the present study was to evaluate the antifungal effects of home-generated ozonated water on the adhesion of the C. albicans attached to the surface of the denture base acrylic resins. Materials and Methods: For the purpose of the study, different concentrations of C. albicans were added to the tubes containing acrylic resin blocks, and then incubated for 2 h at 35°C. The samples were assigned into three groups, each of which contained 42 samples, including normal saline (NS) solution as the negative control, nystatin (N) solution as the positive control, and ozonated water as the test group. The samples were washed and placed in an ultrasonic bath. Subsequently, the saline solution was cultured on Sabouraud dextrose agar. The concentrations of Candida were evaluated during the contact times. Results: The test group (i.e., ozonated water) with 114 colony-forming units (CFU) showed a significant reduction of Candida colonies, compared to the NS group with 2,172 CFU. The 120- and 1-minute incubation with ozonated water showed the highest and lowest effects on the viability of Candida adhered to the acrylic resin, respectively. Conclusion: Based on the findings, home-generated ozonated water can be applied to remove the Candida attached to the surface of the denture plates.